Assay for detection and quantification of newcastle disease virus (NDV) by real-time PCR - Omar, Abdul Rahman; Ideris, Aini; Mohd Yusoff, Khatijah; Tan, Sheau Wei (2007)

(untitled)
The present invention provides a method to detect and quantify the presence or absence of Newcastle Disease Virus (NDV) in biological samples using real-time PCR. In the present invention designed primers were used to detect the presence or absence of the NDV. The primers were designed to specifically amplify DNA fragments from NDV cDNA. In addition, the present invention also provides a kit containing such primers for detecting NDV.